Study of shock waves generation, hot electron production and role of parametric instabilities in an intensity regime relevant for the shock ignition. (March 2016) - Antonelli, L; Köster, P; Folpini, G; Maheut, Y; Baffigi, F; Cristoforetti, G; Labate, L; Levato, T; Gizzi, L A; Consoli, F; De Angelis, R; Kalinowska, Z; et al.
Abstract: We present experimental results at intensities relevant to Shock Ignition obtained at the sub-ns Prague Asterix Laser System in 2012. We studied shock waves produced by laser-matter interaction in presence of a pre-plasma. We used a first beam at 1ω (1315 nm) at 7 x 10 13 W/cm 2 to create a pre-plasma on the front side of the target and a second at 3ω (438 nm) at ∼ 10 16 W/cm 2 to create the shock wave. Multilayer targets composed of 25 (or 40 µ m) of plastic (doped with Cl), 5 µ m of Cu (for K α diagnostics) and 20 µ m of Al for shock measurement were used. We used X-ray spectroscopy of Cl to evaluate the plasma temperature, K α imaging and spectroscopy to evaluate spatial and spectral properties of the fast electrons and a streak camera for shock breakout measurements. Parametric instabilities (Stimulated Raman Scattering, Stimulated Brillouin Scattering and Two Plasmon Decay) were studied by collecting the back scattered light and analysing its spectrum. Back scattered energy was measured with calorimeters. To evaluate the maximum pressure reached in our experiment we performed hydro simulations with CHIC and DUED codes. The maximum shock pressure generated in our experiment at the front side of the target during laser-interaction is 90 Mbar. The conversion efficiency into hot electrons was estimated to be of the order of ∼ 0.1% and their mean energy in the order ∼50 keV.